Experimental restoration of ultrasonic tomograms by modified Wiener filtres - JAN, J. (Archives of Acoustics, 1992)
On the basis of the experimentally identified imaging properties, esp. point-spread-function and image and noise spectra, Wiener-type filters have been designed and applied to ultrasonograms of artificial or tissue-phantom objects. The derived type of filters are advantageous in not needing the average power cross-or autospectrum involving the properties of the undistorted image that is difficult to provide experimentally. It has been found that the filters yield quite unacceptable images due to the amplification of noise but simple modifications of their transfer characteristics suppressing the influence of zeroes in the transfer function of the imaging system enable to obtain substantially better results. Considerable improvement in resolution is possible in spite of the strong nonlinearities involved in the image forming process. Suppressing speckle textures on the basis of differences between average power spectrum of the noise and of the useful image structures has shown only a modest success possibly due to rather small extend of the used image-and spectra matrices and also because of low extent of data not providing good spectral estimates.